Care For Bronchopneumonia In An. RFM With Chest Physiotherapy In The Gardenia Room Of Muhammad Sani General Hospital - Dewita Sinaga; Ratna Dewi Silalahi (Jurnal Ilmiah Kesehatan Mandira Cendikia, 2025)
Bronchopneumonia is one of the lower respiratory tract infections that often affects children and can cause serious complications if not treated properly. The accumulation of secretions in the respiratory tract can cause ineffective airway clearance, shortness of breath, and decreased lung ventilation function. This case study aims to describe the nursing care provided to 7-year-old RFM with bronchopneumonia who underwent chest physiotherapy in the Gardenia Room at Muhammad Sani Regional General Hospital. The method used was a nursing process approach that included assessment, diagnosis, intervention, implementation, and evaluation of nursing care. Three main nursing diagnoses were identified: ineffective airway clearance, hyperthermia, and nutritional deficiency. Interventions included chest physiotherapy, oxygen therapy, antipyretic administration, temperature monitoring, and nutrition and feeding position education. The three-day evaluation showed clinical improvement, including decreased respiratory rate, reduced additional breath sounds, improved body temperature, and increased appetite. This study emphasizes the importance of the role of nurses in applying chest physiotherapy as an effective non-pharmacological intervention to improve airway clearance in children with bronchopneumonia.